Perdebatan Teori Rasionalitas dalam Menjelaskan Terbentuknya Biaya Transaksi pada Seleksi Pegawai Negeri - Firmansyah, M.; Suman, Agus; Manzilati, Asfi; Susilo, Susilo (UI Scholars Hub, 2012)
A civil servant selection attributes transaction cost. Aim of this conceptual paper is to explain behavior of transaction cost payment from perspective theory of the rationale of economics. This study was conducted by understanding various theories regarding a phenomena of transaction cost payment. This study revealed transaction cost payment as typical self interest and utility maximization (neo-classic rationality), to behave as Al-Nafs Al-Ammarah (Islamic rationality). The transaction cost payment was encouraged by perception, understanding and prior experiences (Keynes rationality), environment (psychology rationality). However, there was a limited scope of information for transaction cost payment (bounded rationality).